2012
DOI: 10.1002/acr.21737
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of self‐management of low back pain: Systematic review with meta‐analysis

Abstract: There is moderate-quality evidence that self-management has small effects on pain and disability in people with LBP. These results challenge the endorsement of self-management in treatment guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 40 publications
8
97
0
2
Order By: Relevance
“…Although no significant effect on pain was reported by Du et al, 195 Oliveira et al 196 found evidence to support a small, statistically significant effect at short-and longer-term follow-up. The impact of the interventions on disability was more consistently positive across the two reviews, with two of the three RCTs included in Du et al's review finding significant, small benefits (Du et al calls these 'moderate') in the medium term (6 months), 195 and Oliveira et al 196 reporting small, significant effects in the short and longer term.…”
Section: Explicit Self-managementmentioning
confidence: 84%
See 4 more Smart Citations
“…Although no significant effect on pain was reported by Du et al, 195 Oliveira et al 196 found evidence to support a small, statistically significant effect at short-and longer-term follow-up. The impact of the interventions on disability was more consistently positive across the two reviews, with two of the three RCTs included in Du et al's review finding significant, small benefits (Du et al calls these 'moderate') in the medium term (6 months), 195 and Oliveira et al 196 reporting small, significant effects in the short and longer term.…”
Section: Explicit Self-managementmentioning
confidence: 84%
“…The impact of the interventions on disability was more consistently positive across the two reviews, with two of the three RCTs included in Du et al's review finding significant, small benefits (Du et al calls these 'moderate') in the medium term (6 months), 195 and Oliveira et al 196 reporting small, significant effects in the short and longer term.…”
Section: Explicit Self-managementmentioning
confidence: 94%
See 3 more Smart Citations